DNA-SIP identification of phenanthrene-degrading bacteria undergoing bioaugmentation and natural attenuation in petroleum-contaminated soil. (March 2021) - Liang, Jidong; Gao, Sha; Wu, Zijun; Rijnaarts, Huub H.M.; Grotenhuis, Tim
Abstract: DNA-stable isotope probing (SIP) with 13 C labeled phenanthrene (PHE) as substrate was used to identify specific bacterial degraders during natural attenuation (NA) and bioaugmentation (BA) in petroleum contaminated soil. BA, with the addition of a bacterial suspension mixture named GZ, played a significant role in PHE degradation with a higher PHE removal rate (∼90%) than that of NA (∼80%) during the first 3 days, and remarkably altered microbial communities. Of the five strains introduced in BA, only two genera, particularly, Ochrobactrum, Rhodococcus were extensively responsible for PHE-degradation. Six ( Bacillus sp ., Acinetobacter sp., Xanthomonas sp., Conexibacter sp., Acinetobacter sp. and Staphylococcus sp . ) and seven ( Ochrobactrum sp., Rhodococcus sp., Alkanindiges sp ., Williamsia sp ., Sphingobium sp., Gillisia sp. and Massilia sp.) bacteria responsible for PHE degradation were identified in NA and BA treatments, respectively. This study reports for the first time the association of Xanthomonas sp ., Williamsia sp ., and Gillisia sp . to PHE degradation. Highlights: Phenanthrene degraders were identified by DNA-SIP. Three bacterial genera for phenanthrene degradation were firstly identified. DNA-SIP discovered two of five strains introduced in BA win out and kept function. Shift in bacterial community of soil during NA and BA was observed.